2016
DOI: 10.3389/fnhum.2016.00244
|View full text |Cite
|
Sign up to set email alerts
|

Lateral–Medial Dissociation in Orbitofrontal Cortex–Hypothalamus Connectivity

Abstract: The orbitofrontal cortex (OFC) is involved in cognitive functions, and is also closely related to autonomic functions. The OFC is densely connected with the hypothalamus, a heterogeneous structure controlling autonomic functions that can be divided into two major parts: the lateral and the medial. Resting-state functional connectivity has allowed us to parcellate the cerebral cortex into putative functional areas based on the changes in the spatial pattern of connectivity in the cerebral cortex when a seed poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 82 publications
0
27
0
2
Order By: Relevance
“…The parcellation analyses based on boundary mapping (Margulies et al, 2007;Cohen et al, 2008;Biswal et al, 2010;Hirose et al, 2012Hirose et al, , 2013Hirose et al, , 2016Wig et al, 2014b;Laumann et al, 2015;Poldrack et al, 2015;Glasser et al, 2016;Gordon et al, 2016Gordon et al, , 2017Osada et al, 2017;Ogawa et al, 2018) were applied to the cerebral cortical surface using the preprocessed resting-state data. A fiducial surface image was generated from the middle of the gray matter identified within a functional image for each subject using Caret software (brainvis.wustl.edu/wiki/index.php/Caret:About).…”
Section: Methodsmentioning
confidence: 99%
“…The parcellation analyses based on boundary mapping (Margulies et al, 2007;Cohen et al, 2008;Biswal et al, 2010;Hirose et al, 2012Hirose et al, , 2013Hirose et al, , 2016Wig et al, 2014b;Laumann et al, 2015;Poldrack et al, 2015;Glasser et al, 2016;Gordon et al, 2016Gordon et al, , 2017Osada et al, 2017;Ogawa et al, 2018) were applied to the cerebral cortical surface using the preprocessed resting-state data. A fiducial surface image was generated from the middle of the gray matter identified within a functional image for each subject using Caret software (brainvis.wustl.edu/wiki/index.php/Caret:About).…”
Section: Methodsmentioning
confidence: 99%
“…Functional analyses of the lateral OFC revealed that this region is involved in the processing of gustatory, olfactory or somatosensory rewarding stimuli but also the processing of emotional punishments, evaluating and updating the emotional status, maintaining social behavior, active retrieval of information, semantic processing, verb generation, processing of stimuli that have a coherent temporal structure, music listening, assigning value to certain things and events and decision-making (Papathanassiou et al, 2000;Levitin and Menon, 2003;Kringelbach and Rolls, 2004;Petrides, 2005;Campbell-Meiklejohn et al, 2012;Alluri et al, 2013;Liu et al, 2015;Neubert et al, 2015;Rolls et al, 2015;Hirose et al, 2016). Tasks that require quick responses while retrieving information from the long-term and working memory also showed activations in the lateral OFC.…”
Section: Introductionmentioning
confidence: 99%
“…The OFC has been shown to be connected both directly and indirectly with the hypothalamus (Ongur and Price, 2000; Barbas, 2007), with the lateral OFC showing the greatest connectivity to the lateral hypothalamus (LH) (Hirose et al, 2016). One of the best characterized neuropeptide systems in the LH is the melanin-concentrating hormone (MCH) system.…”
Section: Introductionmentioning
confidence: 99%